The Role of Innovation and Product Quality in Increasing Competitive Advantage - Rifan Rahmat Ramdani; Galih Abdul Fatah Maulani; Lindayani Lindayani (Entrepreneurship Faculty, Universitas Garut, 2025)
This study is intended to test the influence of Product Innovation and Product Quality on Competitive Advantage in Leather Craft MSMEs in Sukaregang Garut Regency. The purpose of this study is to find out the influence of Product Innovation and Product Quality on Competitive Advantage in Sukaregang Leather Handicraft MSMEs in Garut Regency. The population in this study are MSME actors in the Leather Crafts of Garut Regency. The research method used in this study uses a quantitative approach with a non-experimental or survey research design. The sample used in this study is as many as 71 respondents, this study uses a questionnaire as a research tool distributed directly and using a google form to the respondents then processed using SPSS version 25 using the purposive sampling technique. This study uses a research instrument test, a classical assumption test, a multiple linear test and a hypothesis test. The results of the study stated that the product innovation variable had an influence of 23.7% on competitive advantage. The product quality variable has an influence of 22.9% on competitive advantage, and the variable of product innovation and product quality simultaneously has an influence of 28% on competitive advantage and 72% is influenced by other variables not mentioned in this study.